Complete testicular feminization a case report and review of the literature - (:unkn) unknown (My University, 2004)
Complete Testicular Feminization (CTF) is an androgen receptor function disorder. The diagnosis may be made in the postpubertal period on the basis of clinical and hormonal findings accompanying amenorrhea, a karyotype analysis of 46 XY with a female phenotype and absence of pubic hair or inguinal hernias containing testes. In patients with CTF, bilateral undescended testes carry a high risk for malignancy and the risk of malignant transformation of the gonads in adult life is well documented. Testicular feminization often can lead to problems in relations or marriages, and even sometimes result in social disasters. Physicians must be very careful in selecting correct words in order to explain the situation to the patient and family, especially in conservative societies. Here, we present a case of a 30-year old woman with primary amenorrhea who was diagnosed as CTF and underwent bilateral orchiectomy.
Keywords: Androgen receptor function disorders; Complete testicular feminization; Pseudohermaphroditism